Shop Floor Planning and Control in Team-based Work Processes - Riezebos, Jan (International Journal of Industrial Engineering and Management, 2013)
roduction planning and control at the level of shop floor operations requires robust methods that are able to cope with variation in processing times, routing sequences, disturbances, resource allocation, et cetera. Nowadays, many organizations have invested in complex and expensive ERP systems, but the applicability of their shop floor control modules still lags behind the required performance and flexibility. Modern production concepts such as Lean Production and Quick Response Manufacturing advocate the use of team-based work processes and simple production control methods to manage the flow of orders at the shop floor. This paper investigates some of the fundamental principles that are behind this type of methods. We start with the concepts of Period Batch Control and Kanban, both of which were developed before the MRP crusade started. Next we will describe some recent developments in the use of shop floor control methods in Lean and Quick Response Manufacturing, such as Polca, M-Conwip, and Work Load Control. Article history: Received (28 April 2013); Revised (20 May 2013); Accepted (27 May 2013)